The Effect of Industry-Finance Integration on Total Factor Productivity in the Circulation Sector - Geng, Qiangyan (Journal of Global Economy, Business and Finance, 2026)
This research examines the role of industry-finance integration—the deep convergence between the real economy (circulation sector) and financial resources—in enhancing total factor productivity (TFP) within China’s circulation sector. Based on panel data from Chinese provinces between 2016 and 2023, the study employs a two-way fixed effects model and mediation analysis to investigate both direct and indirect channels through which financial integration influences productivity. The findings indicate that industry-finance integration significantly promotes TFP growth, primarily by alleviating financing constraints, fostering technological innovation, and improving resource allocation efficiency in circulation enterprises. These results remain robust after controlling for regional heterogeneity and potential endogeneity. The paper concludes with policy recommendations aimed at deepening financial system reform, optimizing credit allocation, and developing tailored financial products to support the circulation sector’s transition toward intelligent, scale-driven, and high-quality development.